\[\boxed{\text{135\ (135).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 3(4x + 9) + 15 > 7(8 - x)\]
\[12x + 27 + 5 > 56 - 7x\]
\[19x > 56 - 32\]
\[19x > 24\]
\[x > \frac{24}{19}\]
\[Ответ:x \in \left( 1\frac{5}{19};\ + \infty \right).\]
\[2)\ (2 - y)(3 + y) \leq\]
\[\leq (4 + y)(6 - y)\ \]
\[6 + 2y - 3y - y^{2} \leq\]
\[\leq 24 - 4y + 6y - y^{2}\]
\[- y - y^{2} - 2y + y^{2} \leq 24 - 6\]
\[- 3y \leq 18\]
\[y \geq - 6\]
\[Ответ:x \in \lbrack - 6;\ + \infty).\]
\[3)\ (y + 3)(y - 5) -\]
\[- (y - 1)^{2} > - 16\]
\[y^{2} - 5y + 3y - 15 -\]
\[- y^{2} + 2y - 1 + 16 > 0\]
\[0 > 0 - неверно.\]
\[Ответ:\ \varnothing.\]
\[4)\ \frac{3x - 7}{5} - 1 \geq \frac{2x - 6}{3}\ \ | \cdot 15\]
\[3 \cdot (3x - 7) - 15 \geq 5 \cdot (2x - 6)\]
\[9x - 21 - 15 - 10x + 30 \geq 0\]
\[- x - 6 \geq 0\]
\[- x \geq 6\]
\[x \leq - 6\]
\[Ответ:x \in ( - \infty; - 6\rbrack.\]
\[5)\ \frac{2x}{3} - \frac{x - 1}{6} - \frac{x + 2}{2} < 0\ | \cdot 6\]
\[4x - x + 1 - 3x - 6 < 0\]
\[0x < 5\]
\[Ответ:x \in ( - \infty;\ + \infty).\]
\[6)\ \frac{y - 1}{2} - \frac{2y + 1}{8} - y < 2\ \ | \cdot 8\]
\[4y - 4 - 2y - 1 - 8y < 16\]
\[- 6y - 5 < 16\]
\[- 6y < 21\]
\[y > - \frac{21}{6}\]
\[y > - 3\frac{3}{6}\]
\[y > - 3,5\]
\[Ответ:y \in ( - 3,5; + \infty).\]
\[\boxed{\mathbf{135.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ x^{4} - 5x^{2} + 4 = 0\]
\(\left\{ \begin{matrix} x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ t² - 5t + 4 = 0 \\ \end{matrix} \right.\ \)
\(t_{1} + t_{2} = 5,\ \ t_{1} \cdot t_{2} = 4,\ \ \)
\[t_{1} = 4,\ \ t_{2} = 1\]
\[\left\{ \begin{matrix} (t - 4)(t - 1) = 0 \\ x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[Ответ:\ x = \pm 2;\ x = \pm 1.\]
\[2)\ x^{4} - 5x^{2} + 6 = 0\]
\(\left\{ \begin{matrix} x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ t² - 5t + 6 = 0 \\ \end{matrix} \right.\ \)
\(t_{1} + t_{2} = 5,\ \ t_{1} \cdot t_{2} = 6,\ \ \)
\[t_{1} = 3,\ \ t_{2} = 2\]
\[Ответ:x = \pm \sqrt{3};\ x = \pm \sqrt{2}.\ \]
\[3)\ x^{4} - 8x^{2} - 9 = 0\]
\(\left\{ \begin{matrix} x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ t² - 8t - 9 = 0 \\ \end{matrix} \right.\ \)
\[t_{1} + t_{2} = 8,\ \ t_{1} \cdot t_{2} = - 9,\ \ \]
\[t_{1} = 9,\ \ t_{2} = - 1\]
\[Ответ:x = 3;\ x = - 3.\ \]
\[4)\ x^{4} + 14x^{2} - 32 = 0\]
\(\left\{ \begin{matrix} x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ t² + 14t - 32 = 0 \\ \end{matrix} \right.\ \)
\(t_{1} + t_{2} = - 14,\ \ t_{1} \cdot t_{2} = - 32,\ \ \)
\[t_{1} = - 16,\ \ t_{2} = 2\]
\[\left\{ \begin{matrix} (t + 16)(t - 2) = 0 \\ x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[Ответ:x = \pm \sqrt{2}\text{.\ }\]
\[5)\ 4x^{4} - 9x^{2} + 2 = 0\]
\(\left\{ \begin{matrix} x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ 4t² - 9t + 2 = 0 \\ \end{matrix} \right.\ \)
\[D = 81 - 32 = 49,\ \ \]
\[t_{1} = \frac{9 + 7}{8} = 2,\ \ \]
\[t_{2} = \frac{9 - 7}{8} = \frac{1}{4}\]
\[\left\{ \begin{matrix} 4 \cdot (t - 2)\left( t - \frac{1}{4} \right) = 0 \\ x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[Ответ:x = \pm \frac{1}{2};x = \pm \sqrt{2}\text{.\ }\]
\[6)\ {3x}^{4} + 8x^{2} - 3 = 0\]
\[\left\{ \begin{matrix} x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ 3t² + 8t - 3 = 0 \\ \end{matrix} \right.\ \]
\[D = 64 + 36 = 100,\ \ \]
\[t_{1} = \frac{- 8 + 10}{6} = \frac{1}{3},\ \ \]
\[t_{2} = \frac{- 8 - 10}{6} = - 3\]
\[\left\{ \begin{matrix} 3 \cdot \left( t - \frac{1}{3} \right)(t + 3) = 0 \\ x^{2} = t\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[Ответ:x = \pm \frac{1}{\sqrt{3}}\text{.\ }\]